Greenland Ice Sheet solid ice discharge from 1986 through 2017 - K. D. Mankoff; W. Colgan; A. Solgaard; N. B. Karlsson; A. P. Ahlstrøm; D. van As; J. E. Box; S. A. Khan; K. K. Kjeldsen; J. Mouginot; R. S. Fausto (Earth System Science Data, 2019)
We present a 1986 through 2017 estimate of Greenland Ice Sheet ice discharge. Our data include all discharging ice that flows faster than 100 m yr−1 and are generated through an automatic and adaptable method, as opposed to conventional hand-picked gates. We position gates near the present-year termini and estimate problematic bed topography (ice thickness) values where necessary. In addition to using annual time-varying ice thickness, our time series uses velocity maps that begin with sparse spatial and temporal coverage and end with near-complete spatial coverage and 6 d updates to velocity. The 2010 through 2017 average ice discharge through the flux gates is ∼488±49<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="9c7c84ef1601a73265ed1bbd562775fa"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-11-769-2019-ie00001.svg" width="54pt" height="10pt" src="essd-11-769-2019-ie00001.png"/></svg:svg> Gt yr−1. The 10 % uncertainty stems primarily from uncertain ice bed location (ice thickness). We attribute the ∼50 Gt yr−1 differences among our results and previous studies to our use of updated bed topography from BedMachine v3. Discharge is approximately steady from 1986 to 2000, increases sharply from 2000 to 2005, and then is approximately steady again. However, regional and glacier variability is more pronounced, with recent decreases at most major glaciers and in all but one region offset by increases in the NW (northwestern) region. As part of the journal's living archive option, all input data, code, and results from this study will be updated when new input data are accessible and made freely available at https://doi.org/10.22008/promice/data/ice_discharge.